2017
DOI: 10.4236/ajps.2017.88131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cross-Inoculation on Groundnut and Bambara Groundnut-<i>Rhizobium</i> Symbiosis: Contribution to Plant Growth and Yield in the Field at Sarh (Chad) and Ngaoundere (Cameroon)

Abstract: In the context of sustainable research aiming at improving seed yield and maintaining soil fertility, a study on cross-inoculation of groundnut (Arachis hypogaea L.) and Bambara groundnut (Vigna subterranea (L.) Verd.) with rhizobia strains from four crop legumes was carried out at Sarh (Chad) and Ngaoundere (Cameroon). The experiment was conducted in each site following a randomized complete block design with 6 treatments known as the control, and 5 cross-inoculation formulations (RA, RN, RS, RV and MR), each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
5
9
1
Order By: Relevance
“…Our data unveiled a significantly higher biological yield and mycorrhizal dependency in mycorrhizal lemongrass compared to uninoculated ones. The obtained data are in agreement with our previous data indicating an accumulated biomass in mycorrhizal lemongrass compared to non-inoculated control ( Fokom et al, 2019 ), and further lay emphasis on the impact of AMF in improving the growth of many higher plants on earth ( Ngakou et al, 2007 ; Nana et al, 2015b ; Gomoung et al, 2017 ). Tentative explanation of such trait has pointed out foremost mycorrhiza (up to 43% colonization rate relative to the normal control) with their subsequent established repercussion on plant fitness.…”
Section: Discussionsupporting
confidence: 92%
“…Our data unveiled a significantly higher biological yield and mycorrhizal dependency in mycorrhizal lemongrass compared to uninoculated ones. The obtained data are in agreement with our previous data indicating an accumulated biomass in mycorrhizal lemongrass compared to non-inoculated control ( Fokom et al, 2019 ), and further lay emphasis on the impact of AMF in improving the growth of many higher plants on earth ( Ngakou et al, 2007 ; Nana et al, 2015b ; Gomoung et al, 2017 ). Tentative explanation of such trait has pointed out foremost mycorrhiza (up to 43% colonization rate relative to the normal control) with their subsequent established repercussion on plant fitness.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Argaw (2012) indicated that Rhizobium leguminosarum isolated from some Ethiopian soils was able to significantly increase plant performances through nodule numbers, nodule dry biomasses, plant dry biomasses and yields, just like Waheed et al (2014) in a related research on pea crop in comparison to the negative control in Pakistan. Once again, this cross-inoculation experiment has confirmed the promiscuous status of rhizobia associated to food/tree crop legumes, similar to the same findings between four food crops legumes as pointed out by Gomoung et al (2017).…”
Section: Responses Of Plants To Cross-nodulationsupporting
confidence: 88%
“…In a research conducted in Chad and Cameroon, the inoculation of Bambara groundnut and groundnut in the field shows that inoculation contributed to the improvement of growth traits and biomass yield of the two legumes as well as their yield and yield components with a mean value of 63.73 kg/ha for groundnut and 72.71 kg/ha for Bambara groundnut, which is related to the results recorded in this study (Gomoung et al, 2017). In another study conducted in South Africa, inoculating B. japonicum and Bacillus subtilis strains on Bambara groundnut and cowpea revealed that co-inoculation of B. japonicum and Bacillus subtilis strains had the potential to improve the yield of both Bambara groundnut and cowpea (Nelwamondo, 2020).…”
Section: Further Studies On Improving Legume Production Using Inocula...supporting
confidence: 88%